(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Background: Since December 2019, a novel coronavirus disease (COVID-19) began its journey around the world. Since then, many efforts are being carried out to contain the virus. Knowledge and attitude of people should be directed towards strict preventive practices in order to halt the spread of the virus. Medical students, as frontline healthcare workers, are more susceptible to be infected by the virus. The aim of the current cross-sectional study is to assess the knowledge, practice and attitude of 2nd year medical students from medical college in tribal part of Gujarat, India, regarding dead body management of covid-19 patients. Methods: A self-designed questionnaire consisting of 19 questions was developed and given to the students. The knowledge, attitude, and practice of the participants were investigated. Results: A total of 235 medical students completed the questionnaire. Out of the total participants (n=235), 133(56.6%) were male and 102(43.4%) were female. 88.9% of students knew the fact that covid-19 dead body is infective, 94.5% students are aware about specific guidelines for dead body management of covid-19 patients, 40% students have no knowledge about Medico-legal